Textual coherence in the production of oral and written stories - Spinillo, Alina Galvao; Martins, Raul Aragao [UNESP]; Correa, Jane (Univ Fed Rio Janeiro, 2021)
This study examined the establishment of coherence in the production of stories in oral and written modality produced by middle-class children, attending the 2nd and 5th grades of elementary school. The students produced sotires in both modalities that were classified into hierarchical categories according to the level of coherence they presented. There was an interaction between schooling and production modality: the texts produced by 2nd graders presented the same level of coherence in both modalities, while the 5th grade children's texts presented a higher level of coherence when produced in writing than orally. Schooling had a positive effect on both oral and written production. It was concluded that the modality of production influences only the most proficient writers, who consider the written material revisable, while novice writers do not perceive this possibility. Educational implications are discussed regarding learning to write texts.
Keywords: Textual Coherence; Oral Stories; Written Stories; Children